2020
DOI: 10.31234/osf.io/z8cvx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Transcendence and Life Stories of Humanistic Growth Among Late-Midlife Adults

Abstract: Objective: Self-transcendence is the experience of feeling connected to something greater than oneself. Previous studies have shown high scores on self-transcendence are associated with well-being and other psychological benefits, but have rarely examined the lived experiences of highly self-transcendent people. Method: Black and White men and women in late-midlife completed Life Story Interviews and self-report measures of self-transcendence. In Study 1 (N = 144, Mage = 56.4), we used grounded theory methodol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…This further resonates with Reischer et al’s (2019) finding that those high in self-transcendence narrate varied life experiences with greater emphasis on deepened self-understanding than those low in self-transcendence. These diverse findings contrast the view that awe results in an attentional self–other dichotomy; clearly, awe can result in enhanced self-understanding (involving attention to the self) in addition to increased concern for others, which together reflect an appreciation for interdependence concerns.…”
Section: What Is Meant By the Self?supporting
confidence: 69%
See 1 more Smart Citation
“…This further resonates with Reischer et al’s (2019) finding that those high in self-transcendence narrate varied life experiences with greater emphasis on deepened self-understanding than those low in self-transcendence. These diverse findings contrast the view that awe results in an attentional self–other dichotomy; clearly, awe can result in enhanced self-understanding (involving attention to the self) in addition to increased concern for others, which together reflect an appreciation for interdependence concerns.…”
Section: What Is Meant By the Self?supporting
confidence: 69%
“…Narrative researchers have begun to investigate phenomena that bear conceptual similarities to awe, although this work is in its infancy. For example, Reischer, Roth, Villarreal, and McAdams (2019) conducted a qualitative analysis of life story episodes (see McAdams, 1993) to uncover the prototypical narrative themes associated with self-transcendence. They found that four themes marked the life stories of those who reported the highest scores on a measure assessing self-transcendence.…”
Section: What Is Meant By the Self?mentioning
confidence: 99%
“…The second theme reflects evidence that Agreeableness is associated with greater acceptance of life, ability to adjust, and cross-domain satisfaction. Acceptance of life as it is is a noted correlate of self-transcendence (Reed, 2013; Reischer et al, 2021). Agreeableness is not only associated with greater acceptance of others but also of oneself (self-acceptance), one’s circumstances (quality of life), and one’s works (personal accomplishment, authentic pride).…”
Section: Discussionmentioning
confidence: 99%
“…Self-transcendence can be observed not only through self-report but also through narrative identity (Reischer et al, 2023(Reischer et al, , 2021, the evolving story of self that individuals use to make meaning out of life (McAdams and McLean, 2013). Structural, affective, and thematic aspects of the narrated life story reflect aspects of an individual's personality (McLean et al, 2020).…”
Section: Self-transcendence In Personal Narrativesmentioning
confidence: 99%
“…Healthy individuals who score high in self-reported self-transcendence narrate their life stories with strong themes of closure (acceptance of life as it has been lived), self-actualization (congruence with and satisfaction with the self), spiritual pluralism (ideologically inclusive, personal spirituality), and interconnectedness (interpersonal connectedness) (Reischer et al, 2021), all of which positively correlate with psychological well-being and life satisfaction and negatively correlate with depression (Reischer et al, 2017).…”
Section: Self-transcendence In Personal Narrativesmentioning
confidence: 99%